Factors Influencing EFL Student’s Boredom in Reading Academic Journal - Nurul jannah; Citra Prasiska Puspita Tohamba; Syarif Amin; Yuliana Sain (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Reading academic journals is an important part of academic life, especially for students. However, many students feel bored in reading academic journals, which can affect their academic performance. This study aims to find out the factors that influence students' boredom in reading academic journals, and to find out the strategies used by students in overcoming boredom in reading academic journals. The research method used a qualitative approach with a descriptive type. The participants in this study were four students majoring in English at Universitas Muhammadiyah Kendari. Data collection used interviews. Based on the results of the study, it was found that there are two factors that affect the boredom of students reading academic journals, namely internal factors and external factors, the first internal factor is 1) Lack of enthusiasm; 2) laziness; 3) motivation. The second factor, on the other hand, is external, and includes things 1) writing-related aspects, 2) vocabulary, 4) difficult-to-understand language, and 5) family. Students use various strategies to overcome boredom when reading academic journals, such as engaging in physical activities, clearing their minds, playing games, watching movies, finding a comfortable place to read, setting reading goals, reading simple texts, planning the right moment, listening to music.